Усовершенствование системы автоматической подачи твердого топлива и активатора горения в топку котла тепловых электростанций - Мезеря, Андрей Юрьевич (НТУ "ХПИ", 2016)
У статті розглянуто питання підвищення точності регулювання подачі твердого палива в топку котла теплових електростанцій. Розроблено систему автоматичного регулювання подачі присадок, що активізують процес горіння.

The article examines the question of increasing the accuracy of feed control solid fuel to the boiler furnace of the thermal power station. Developed a system of automatic control of fide additives, which activate the process of burning.
Improving a method of supplying solid fuel and activator of burning in boiler furnace of thermal power
Keywords: КПД; расход топлива; угольная пыль; момент инерции ротора; частота вращения ротора; микропроцессорный измерительный блок; САУ; АСУ